Capital Market Returns and Inflation Nexus in Croatia: Wavelet Coherence Analysis - Bošnjak Mile; Novak Ivan; Bašić Maja (Business Systems Research, 2021)
Background: Hedging against inflation assumes instruments such as gold, stocks, fixed income securities, and real estate. There still exists a lack of appropriate strategy to hedge against inflation.